The effectiveness of a health education intervention to reduce anxiety in quarantined COVID-19 patients: a randomized controlled trial - Imen Zemni; Amel Gara; Hadhba Nasraoui; Meriem Kacem; Amani Maatouk; Oumeyma Trimeche; Hela Abroug; Manel Ben Fredj; Cyrine Bennasrallah; Wafa Dhouib; Ines Bouanene; Asma Sriha Belguith (BMC, 2023)
Abstract Introduction The COVID-19 pandemic is regarded as a serious public health concern that boosts levels of stress and anxiety which could be explained by several reasons, including social isolation. In this regard, we aimed to assess the impact of health education on the anxiety level of COVID-19 patients during the isolation period. Methods This is a randomized controlled trial conducted between February 2021 and June 2021. Patients tested positive for Covid-19 with mild to moderate forms were randomized to Education (n = 267) or control (n = 269). The education group received a phone health education session on day 1 (D1) following the diagnosis. The three components of the health education intervention were an explanation of the coronavirus disease, what to do in the event of complications, and the recommended preventive measures. The two groups received a telephone evaluation of their Hospital Anxiety and Depression scores on D1 and day seven D7 following the positive diagnosis. The primary outcome was the rate of anxiety reduction in each group on D7 based on a HAD-A score ≥ 8. Secondary outcomes were the rate of anxiety reduction on D7 based on a HAD-A score ≥ 11, the percentage of people complying with isolation and the scores of adherences to preventive measures during the isolation in each group. Results Hundred and ninety-six patients in the intervention group and 206 patients in the control group completed the study. The sociodemographic, clinical, and initial anxiety level features of the intervention and control groups were comparable at baseline (p ≥ 0.05). On D7, the education group's anxiety level (HAD-A ≥ 8) decreased from 26 to 16.3% (p = 0.013) while in the control group it increased from 19.4 to 22.8% (p = 0.37). Thus, the percentage change in anxiety between D1 and D7 (delta D7 - D1) was − 9.7% in the Education group and + 3.4% in the Control group. Using the HAD-A ≥ 11 thresholds, the percentage of anxiety decreased from 15.3 to 11.2% (p = 0.26) between D1 and D7, while it increased in the control group from 9.7 to 15.7% (p = 0.045). Thus, the education group's change in anxiety (delta D7 - D1) was − 4.1%, while the control group's change was + 6%. Conclusion During an outbreak, providing health education to quarantined patients may be beneficial to reduce the psychological impact of the disease. Trial registration number ClinicalTrials.gov Identifier: NCT05715593, retrospectively registered on 8/02/2023 https://clinicaltrials.gov/ct2/results?term=NCT05715593&Search=Search .